2022
DOI: 10.3389/fonc.2022.941156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of necroptosis-related genes for predicting prognosis and exploring immune infiltration landscape in colon adenocarcinoma

Abstract: BackgroundNecroptosis is a recently discovered form of cell death that plays an important role in the occurrence and development of colon adenocarcinoma (COAD). Our study aimed to construct a risk score model to predict the prognosis of patients with COAD based on necroptosis-related genes.MethodsThe gene expression data of COAD and normal colon samples were obtained from the Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx). The least absolute shrinkage and selection operator (LASSO) Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Zhang et al [ 31 ] reported that PRMT1 inhibited immune escape of colon cancer cells by enhancing RIP3 methylation. In addition, previous studies have shown that many NRGs had potential value in predicting the prognosis of COAD patients [ 32 , 33 ]. Therefore, studying the correlation between necroptosis and immune regulation in COAD can provide new therapeutic strategies for patients with COAD.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 31 ] reported that PRMT1 inhibited immune escape of colon cancer cells by enhancing RIP3 methylation. In addition, previous studies have shown that many NRGs had potential value in predicting the prognosis of COAD patients [ 32 , 33 ]. Therefore, studying the correlation between necroptosis and immune regulation in COAD can provide new therapeutic strategies for patients with COAD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the important role of coagulation-related factors in bladder cancer has not been reported yet. AGING It has been proved feasible to construct a risk signature with the expression of key genes to monitor the tumor and its microenvironment state [5][6][7]. We divided bladder cancer into two states of hypercoagulability and low coagulation by clustering coagulation-related genes, and we found that hypercoagulability presaged a poor prognosis of bladder tumors.…”
Section: Introductionmentioning
confidence: 99%